Imagens institucionais da modernidade: a educação profissional em Goiás (1910-1964) - Pires, Mauro Alves (2014)
This research investigates the images that institute, make cohesive and legitimize the professional education in Goiás on the first half of the twentieth century. It is focused on the establishment of the modern institutional imaginary concerning the public professional education. In it, the past is interpreted, the future is planned and the especific politics of the educational field are legitimized by the modern set of ideas. This imaginary produces representations and practices led by rationality and disciplinary action on bodies and on the educational building and are reinforced by rites and institutional images. The space temporal cut of this research goes from the foundation of the Escola de Aprendizes Artifices in Goiás city (1910), analyzing the period of its transference throughout the change of the capital to Goiânia to the foundation of the Escola Técnica Federal de Goiás (1964).